The influence of sad mood induction on task performance and metacognition. Issue 9 (September 2021) - Culot, Catherine; Fantini-Hauwel, Carole; Gevers, Wim
In many situations, the ability to make appropriate metacognitive judgements on our performance is essential to make decisions and adapt our behaviour. Past research suggests a strong relationship between metacognition and emotional disorders such as depression. Depressive disorders have been associated with an underestimation bias: depressive patients report lower confidence in their performance than healthy individuals. It is currently not clear whether the induction of a negative mood in healthy participants has similar consequences. Yet, such knowledge would permit to isolate the causal influence of the negative affect on metacognition, free of all the comorbidities associated with depression. In this study, we used a combination of films, pictures, and recalls to induce negative and neutral moods during a perceptual metacognitive task. Negative mood induction had no impact on the perceptual task. Participants did report lower confidence levels in the negative condition compared with a neutral condition. This study thus confirms a causal relationship between negative affect and metacognitive abilities.